Teaching practice in algorithms and data structures - Martinez, Cristian A.; Nocera, Carlos; Rodriguez, Diego A.; Orozco, Ismael; Xamena, Eduardo (2017 36th International Conference of the Chilean Computer Science Society (SCCC), 2017)
The accreditation of university careers in Argentina has allowed improvements on curricular contents in order to balance and standardize fundamental knowledge that a graduated should have. In this sense, the accreditation of the Systems Analysis degree of the National University of Salta (Argentina) generated positive changes over its curriculum, as well as in technological and postgraduate training, infrastructure, among others. This paper describes experiences in the teaching-learning process related to a subject of the mentioned career.